A Pilot Study of the Use of Pain Questionnaires in Vertebroplasty Research - Gray, L.A.; Kallmes, D.F. (American Journal of Neuroradiology, 2009)
SUMMARY: Administration of comprehensive outcomes measures in elderly patients presenting for vertebroplasty is considered difficult. We administered a battery of 11 outcomes questionnaires with a total of 82 questions, both in person before vertebroplasty and by telephone after vertebroplasty in 20 consecutive patients (mean age, 74.5 years; 80% women). Initial and follow-up interviews required an average of 17.4 ± 0.36 minutes (range, 14–21 minutes) and 27.2 ± 0.73 minutes (range, 16–33 minutes), respectively.